High Performance of Functionalized Graphene Hydrogels Using Ethylenediamine for Supercapacitor Applications - Ju, Hong; Xu, Weihui; Fang, Lu; Duan, Jinzhuo (Frontiers in Chemistry, 2022)
High-performance supercapacitor (SC) electrodes typically require excellent rate capabilities, long cycle life, and high energy densities. In this work, ethylenediamine (EDA) functionalized graphene hydrogels (FGHs) with a high capacitor performance were prepared from graphene oxide (GO) dispersions using a two-step hydrothermal method. In addition, we used a very small amount of EDA to achieve the partial reduction and functional modification of GO, and the synthesized FGH-4 binder-free electrodes exhibited a high specific capacitance of −240 F/g at 1 A/g. We also successfully fabricated a symmetric SC device based on the FGH-4 electrode, with a wide voltage window of 3.0 V. More importantly, the as-assembled symmetric SC delivered a high specific energy of 39 Wh/kg at a specific power of 749 W/kg, while still maintaining its superior cycle life (retaining 88.09% of its initial capacitance after 10,000 cycles).